Development and evaluation of new molecular epidemiological methods for analysis of salmonella TYPHI - Tau, Nomsa Pauline (My University, 2017)
The typhoid fever causing Salmonella Typhi remains an important public health problem in Africa. More importantly, the emergence of the highly antimicrobial resistant H58 Salmonella Typhi haplotype is of greater concern. Rapid and highly discriminatory molecular methods are essential for prompt and effective epidemiological investigation of typhoid fever outbreaks. Traditional methods, such as pulsed-field gel electrophoresis (PFGE) are time-consuming and offer subjective discrimination of highly homologous isolates. On the contrary, molecular subtyping based on multiple-locus variable-number tandem-repeats (VNTR) analysis (MLVA) is a rapid, PCR-based method which has been successfully used for subtyping homogenous isolates of the Salmonella genus. This study describes the development and application of a MLVA assay for molecular characterization of Salmonella Typhi isolates from sub-Saharan Africa (SSA). This involved evaluation of thirteen VNTR loci using a validation panel consisting of 50 diverse Salmonella Typhi isolates. A MLVA assay consisting of five highly variable VNTR loci was adopted. The developed MLVA assay was used, along with PFGE, to characterize 316 Salmonella Typhi isolates from SSA. A total of 226 MLVA types were identified as compared to 143 PFGE fingerprint types. MLVA typing results indicated intracontinental spread of Salmonella Typhi. For the rapid identification of H58 Salmonella Typhi, a conventional PCR targeting a mutation that is exclusive to the H58 haplotype was employed on 105 isolates from South Africa as well as 121 isolates from other SSA countries. Approximately 54% (105/214) of the Salmonella Typhi isolates from South Africa and 62% (75/121) of the isolates from other SSA countries were identified as H58 Salmonella Typhi. The MLVA tool was able to discriminate among H58 Salmonella Typhi isolates. MLVA is viable alternative to PFGE for subtyping Salmonella Typhi and can be used as first-line assay for routine screening of Salmonella Typhi isolates in SSA, providing excellent discrimination of isolates.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of requirements of the degree of Master of Science. Johannesburg, 2017
Keywords: Salmonella Molecular Epidemiology